HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN KETERAMPILAN BERBICARA MAHASISWA PROGRAM STUDI BAHASA JERMAN UNPATTI - Henderika Serpara; Patresia S Apituley; Sarcy Laiwurny (Universitas Pattimura, 2023)
This study aims to collect data and information about the relationship between selfconfidence and speaking skills in German language education study program students of Pattimura University.This study has two variables, namely: independent variable and dependent variable. The population of this research is third semester students and the sample is students who offer Produktiv Sprechfertigkeiten zur Aufbaufstufe course. The data of this study were obtained through speaking tests and questionnaires. Based on data analysis, it shows that r count is greater than r table (0.633>0.482) so the results show that there is a relationship between student confidence and speaking skills in the German language education study program at Pattimura University.